Technical Documentation in Traffic Technology - Čurepić, Danko; Toš, Zdravko (Promet - Traffic&Transportation, 2012)
The requirements for the prompt usage of traffic infrastructure capacities define the technological frames which ensure updated maintenance and development of new traffic infrastructure capacities by implementing graphical and computer systems. Technical documentation (TD) based on the technology of geographic information systems (GIS) allows fast analysis of graphical and alphanumerical data with the aim of identifying spatial relations among various cartographic elements. The paper analyses and presents the methodological bases of building GIS with the aim of designing the traffic network topology, as well as structural and functional analysis which uses the acquired knowledge to propose concrete solutions on connecting data about the position of infrastructure facilities with their properties in the railway traffic safety. KEY WORDS: technical documentation, geographic information system, structural and functional analysis, software for technical drawing, signalling devices, railway